Passion's way ([s.l.] Freyda Rosthstein Production, 1999)
In life you have one true, pure love. One person who captures your heart, and gently touches your soul. For Charles Darrow, this person is Anna Leath and for Anna, this person is Charles. Years ago, their lives strayed apart. Now they are about to reunite.
VHS
Based on the classic novel by Edith Wharton
Executive producer Freyda Rothstein ; directed by Robert Allan Ackerman
Sela Ward, Timothy Dalton, Alicia, Witt, Jamie Glover, Cynthia Harris and Leslie Caron.
Keywords: Love stories; Feature films